Comparison of Antithrombotic Effects of GPIIb-IIIa Receptor Antagonist and TXA2 Receptor Antagonist in the Guinea-pig Thrombosis Model: Possible Role of TXA2 in Reocclusion after Thrombolysis - Takiguchi, Yoshiharu; Asai, Fumitoshi; Wada, Kouichirou; Nakashima, Mitsuyoshi (Thrombosis and Haemostasis, 1995)
The effects of Ro 44-9883, a new specific antagonist of platelet glycoprotein IIb-IIIa receptor, on thrombus formation and reocclusion after thrombolysis induced by tissue-type plasminogen activator (t-PA) were compared with those of vapiprost, a thromboxane (TX) A2 receptor antagonist, using a photochemically-induced thrombosis model in the guinea-pig femoral artery. Pretreatment with Ro 44-9883 (5,10 and 20 μg/kg/min, i. v.) prolonged the time required to occlude the artery in a dose-dependent manner. Ro 44-9883 at 10 and 20 μg/kg/min significantly inhibited ex vivo platelet aggregation in whole blood induced by collagen, ADP or U46619. Vapiprost 0.3 mg/kg inhibited thrombus formation and platelet aggregation induced by collagen or U46619, to the same extent as Ro 44-9883 at the higher doses. In the thrombolysis study, Ro 44-9883 at the higher doses given as comedication with t-PA reduced the time to achieve reperfusion and increased the vascular patency after successful reperfusion. Vapiprost also significantly reduced the time to reperfusion and prevented reocclusion. However, the vascular patency after thrombolysis by t-PA with vapiprost was significantly increased compared with Ro 44-9883. Ro 44-9883 inhibited platelet aggregation, but did not prevent TXA2 formation in platelets. Thus, vascular contraction mediated by platelet-derived TXA2 may be responsible for lower efficacy of Ro 44-9883 against reocclusion compared with vapiprost. These results indicate that not only platelet aggregation but also vasoconstriction may contribute to reocclusion after t-PA-induced thrombolysis in the guinea-pig.